PENERAPAN MODEL PEMBELAJARAN GUIDED DISCOVERY UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS XI SMA N 9 PEKANBARU DALAM PEMBELAJARAN FISIKA - Rahman Bimantara; Muhammad Nasir; M. Rahmad ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed to know enhancement on critical thinking skillssecondary grades students SMA N 9 Pekanbaru through application guideddiscovery learning model in learning physics and to know the difference learningoutcomes between secondary grades students that teached by conventional learningmodel with secondary grades students that teached by guided discovery learningmodel on spring force matter. This research conducted on SMA N 9 Pekanbaru fromJuly to December 2015. This type of research is quasi experimental design withNonequivalent Control Group Design. Sampling technique of this research usedsimple random sampling technic by taking two classes at random from population.The Samples is sciences two as experiment class and sciences four as control class.The number of students on experiment class is 29 childrens which consist of 10 boysand 19 girls.While the number of students on the control class of 30 people consist of12 boys and 18 girls.Multiple choices questions used for collect data as techniquetest. Based on analyze of mean percentage posttest show that mean percentageexperiment class with 71,67 % percentages is different than control class with59,52 % percentages. Based on analyze with t-test, show that thitung > ttabel then Horejected and Ha accepted with a significance level 5 %. Its show that there aredifference learning outcomes between experiment class and control class.Keywords: critical thinking skills, guided discovery learning, conventional learning,spring forces.